Intellectual property law in Africa : harmonising administration and policy - Ncube, Caroline Bongiwe (Routledge-Cavendish research in intellectual property., 2023)
"Examining the harmonisation of Intellectual Property policy, law, and administration in Africa, this book evaluates the effectiveness of efforts to establish continental Intellectual Property institutions and frameworks. It also considers sub-regional initiatives led by the regional economic communities and the regional Intellectual Property organisations, focusing on relevant protocols and agreements that address Intellectual Property as well as the implementing institutions. The book assesses the progress of such initiatives with particular reference to the current socio-economic status of African states. It argues that the harmonisation initiatives need to be crafted in a way that is supportive of the developmental goals of African states and advocates for due consideration of individual states' unique conditions and aspirations"--